2016
DOI: 10.1016/j.neuroimage.2016.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of MRI-guided attenuation correction techniques in time-of-flight brain PET/MRI

Abstract: Purpose: In quantitative PET/MR imaging, attenuation correction (AC) of PET data is markedly challenged by the need of deriving accurate attenuation maps from MR images. A number of strategies have been developed for MRI-guided attenuation correction with different degrees of success. In this work, we compare the quantitative performance of three generic AC methods, including standard 3-class MR segmentation-based, advanced atlasregistration-based and emission-based approaches in the context of brain time-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…In addition, application of dedicated MR sequences enabling to delineate bony structures, such as ultra-short echo time (UTE) 12 or zero time echo (ZTE), 13 in whole-body imaging is not yet clinically feasible owing to the long acquisition time and susceptibility to artifacts when using a large field-of-view. As such, the use of atlas-based methods for identification of bone tissue is common practice in MRI-guided attenuation generation in brain [14][15][16][17] and more importantly in whole-body imaging. [18][19][20] Despite promising potential reported in the literature, we observed that the SBA technique tends to underestimate bone volume identification in a comparative assessment of common atlas-based bone segmentation techniques from MRI using a set of MR/CT image pairs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, application of dedicated MR sequences enabling to delineate bony structures, such as ultra-short echo time (UTE) 12 or zero time echo (ZTE), 13 in whole-body imaging is not yet clinically feasible owing to the long acquisition time and susceptibility to artifacts when using a large field-of-view. As such, the use of atlas-based methods for identification of bone tissue is common practice in MRI-guided attenuation generation in brain [14][15][16][17] and more importantly in whole-body imaging. [18][19][20] Despite promising potential reported in the literature, we observed that the SBA technique tends to underestimate bone volume identification in a comparative assessment of common atlas-based bone segmentation techniques from MRI using a set of MR/CT image pairs.…”
Section: Introductionmentioning
confidence: 99%
“…transmission scan. Although these methods show promise for accurate attenuation correction of PET images from MR-PET scanners in the presence of MR metallic artefacts, they still produce noticeable quantification bias in the context of brain PET imaging(Mehranian, Arabi, & Zaidi, 2016). Although these methods show promise for accurate attenuation correction of PET images from MR-PET scanners in the presence of MR metallic artefacts, they still produce noticeable quantification bias in the context of brain PET imaging(Mehranian, Arabi, & Zaidi, 2016).…”
mentioning
confidence: 99%
“…A synchronized acquisition allows the use of MRI information for attenuation correction (AC) of PET images, though there is no consensus on the best algorithm (Cabello et al, 2016; Mehranian et al, 2016; Ladefoged et al, 2017). Future works will include the proposed AC algorithms in the PET/MRI pipelines of Pypes.…”
Section: Discussionmentioning
confidence: 99%